PENGENALAN AKUNTANSI DASAR UNTUK UMKM - Astiningsih, Della Rohma Dwi; Damayanty, Prisila; Davita, Enza; Sobari, Fajar; Leliyana, Leliyana; Setiawan, Indra (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
MSME in Indonesia are one of the pillars of the Indonesian economy apart from cooperatives. The development of the number of MSME has increased from year to year, but only a few MSME have experienced developments in terms of their financial performance. This is because MSME still have weak knowledge of the process of accounting records and low awareness of the importance of accounting information in world business. Therefore, community service activities in the form of simple accounting introduction training for MSME are still very much needed. This training is intended for SMEs in Jagakarsa. Implementation of activities carried out by using the method of lectures, tutorials, and discussions. The results of this activity indicate that SMEs in Jagakarsa in running their business tend not to practice accounting. Some MSME actors in Jagakarsa also don't understand accounting and what the purpose of making financial reports is. This community service activity helps provide advice, motivation and knowledge to all MSME in Jagakarsa to implement simple training practices in their business activities so that they can improve their financial business performance